Alpha emitting radionuclides in sediment cores from the Western Irish Sea Mud Belt, June 2022 - Hannah C Muir; Claire Evans; David G Reading; Phillip E Warwick (PANGAEA, 2025)
Radionuclide analysis was carried out on freeze-dried sediments sampled at 1 cm resolution from the top 40 cm of 3 sediment cores (Sites 4, 8, 20). Samples were analysed to resolve activity peaks identified by gamma spectrometry. Not all samples were analysed for each 40 cm core section. To prepare samples for alpha spectrometry, an aliquot of sample was spiked with 209Po as a chemical yield monitor and then digested using aqua regia. A clean silver disc was then placed in the resultant digest for 210Po autodeposition. Alpha spectrometry (Ortec Octete) was conducted to measure the radionuclide 210Po. Data acquisition was performed using Genie-2000 (Mirion Canberra) and spectral analysis was performed using Fitzpeaks 32 deconvolution software. Samples were counted for 8 hours to achieve low limits of detection.
In: Muir, Hannah C; Reading, David G; Warwick, Phillip E; Peel, Kate; Evans, Claire (2025): Sediment core data (organic carbon, dry bulk density, grain size, radionuclide) from the Western Irish Sea Mud Belt June 2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983345